GAMIFICATION AND SPEAKING SKILLS: ENHANCING LANGUAGE LEARNING THROUGH PLAY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study examines the impact of gamification on students' speaking skills in ESL/EFL classrooms. Through a survey of 30 university-speaking teachers, the research explores whether game-based learning improves oral proficiency, confidence, and participation. Findings reveal that gamification enhances student engagement, with 62.5% of teachers observing confidence growth and 75% reporting increased participation. However, challenges such as time-consuming preparation and unequal student involvement were noted. The study concludes that gamification should supplement, rather than replace, traditional speaking exercises. By integrating structured lessons with interactive activities, educators can increase learning outcomes and create a more dynamic language-learning environment.